Behcet's disease in an adult male from Nepal: A case report - Madan Basnet (Wiley, 2021)
Abstract This case report highlights considering Behcet's disease as a diagnosis in orogenital ulcers and uveitis, although its prevalence is unknown in Nepal due to underreporting. Also, collaboration for patient care among relevant specialties is required.